The effect of training schedule and playing positions on training loads and game demands in professional handball players - Font, R.; Karcher, C.; Loscos-Fàbregas, E.; Altarriba-Bartés, A.; Peña, J.; Vicens-Bordas, J.; Mesas, J.; Irurtia, A. (Biology of Sport, 2023)
In this research, we aimed to (1) describe the differences in internal and external load between playing positions and (2) characterize the training demands of the days before competitive events for professional handball players. Fifteen players (5 wings, 2 centre backs, 4 backs, and 2 pivots) were equipped with a local positioning system device during training and 11 official matches. External (total distance, high-speed running, player load) and internal loads (rating of perceived exertion) were computed. Substantial differences were recorded between the external load variables depending on each playing position and depending on whether it was a training day (high-speed running: effect size (ES) = 2.07; player load: ES = 1.89) or a match (total distance: ES = 1.27; high-speed running: ES = 1.42; player load: ES = 1.33). Differences in internal load were not substantial. The rating of perceived exertion, at this competitive level, does not seem to discriminate the differences registered in the external load, probably due to the degree of adaptation to the specific effort of these players. The large differences observed in external load variables should be used to tailor practices and better adjust the training demands in professional handball settings.